Report on practice-in-industry training in fish preservation. - Landicho, Erlinda C. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1964)
This report embodies the actual accomplishments of the writer in the field of fish preservation during four months of practice-in-industry training. It is written not only for the purpose of satisfying one of the requirements before graduation, but also to serve as reference for future fishery students, who will specialize in the fish preservation. This paper includes all the actual methods, principles and technique applied by the different factories and establishments, which the author visited. Also, some of the prospectus and layouts of some factories and establishments are included.
Keywords: Fish-Preservation.